Radiation outcome in mechanical thrombectomy of acute ischemic stroke - Cai Xiaoying (De Gruyter, 2019)
Mechanical thrombectomy is recommended for acute ischemic stroke (AIS) with large artery occlusion. Radiation during the endovascular procedure would increase the risk of skin diseases. We sought to identify radiation outcomes during mechanical thrombectomy.